Tinnitus Therapy Based on High-Frequency Linearization Principles – Preliminary Results - POREMSKI, Tomasz; KOSTEK, Bożena (Archives of Acoustics, 2012)
The aim of this work is to present problems related to tinnitus symptoms, its pathogenesis, hypothe-ses on tinnitus causes, and therapy treatment to reduce or mask the phantom noise. In addition, thehypothesis on the existence of parasitic quantization that accompanies hearing loss has been recalled.Moreover, the paper describes a study carried out by the Authors with the application of high-frequencydither having specially formed spectral characteristics. Discussion on preliminary results obtained andconclusions are also contained.